The influence of the river discharge on residence time, exposure time and integrated water fractions for the Tagus estuary (Portugal) - de Pablo, Hilda (2022)
Understanding how long water is retained in an estuary and how quickly it is completely flushed is essential to estimate an estuary's health in areas with significant pollutant loadings. The present study analyses the effect of five different Tagus River discharge scenarios ranging from low to extreme on residence time (RT), exposure time (ET) and integrated water fractions inside pre-established Tagus estuary areas, to identify its most vulnerable areas to pollution. The 3D version of the MOHID hydrodynamic model coupled to a lagrangian tool was used. The increase of the river discharge generated high current velocities which, in turn, led to an increased rate of tracers leaving the estuary. As a consequence, RT and ET decreased from 59 to 3.5 days under a low and extreme river discharge scenario, respectively. Under a low river discharge, significant differences were observed between RT and ET in the areas located in the main body of the estuary and in the bays. As river discharge increased, RT and ET decreased in all areas of the estuary and those differences faded, with the greatest differences observed in the areas situated along the south margin. In general, results showed that with high river discharges the tracers released in the upper estuary are spread throughout the estuary, but mainly in downstream areas. However, when the river discharge reached exceptionally high values, local eddies were formed, leading to the retention of the tracers in the estuary's south margin and inner bays. The results in this study allowed to identify the most vulnerable areas within the estuary as a function of the river discharge.